Impact of industrial noise on occupational health and sustainable solutions - Zurita , Verónica; Bonilla , Dayana; Sifuentes , Jessy; Zambrano, Juliana (SCT Proceedings in Interdisciplinary Insights and Innovations, 2025)
The research project focused on the study of noise pollution and its impact on the occupational health of the employees of the ADELCA factory, located in Machachi, Ecuador. It was identified that industrial noise, generated by machinery and equipment, affected both the physical and psychological health of workers, causing hearing damage and emotional alterations. Through technical visits, data were collected to diagnose the problem and to delimit the research temporally and geographically, proposing measures to reduce noise levels. It became evident that the company did not comply with Ecuadorian environmental regulations regarding maximum noise limits, which implied risks to the health of employees and residents of nearby areas. The project proposed implementing acoustic insulation materials in critical areas to reduce the impact of noise. It also proposed monitoring noise emissions and applying corrective measures to ensure a safer working environment and improve coexistence with the neighboring community. The case was related to similar situations in Argentina, where industries in the metallurgical sector faced noise problems in urban areas. This allowed reflection on the importance of strengthening corporate social responsibility and the implementation of sustainable solutions in both countries